Interaction of actin with plasminogen/plasmin system: mechanisms and physiological role - Tykhomyrov, A.A. (Вiopolymers and Cell, 2012)
In the present review, we have summarized and analyzed the literature data concerning cooperation between
multifunctional proteins, the components of plasminogen/plasmin system and actin. The mechanisms underlying
intermolecular interactions and the role of plasminogen kringle domains in protein-protein recognition are
reviewed. A particular attention is paid to extracellular actin that serves as a surface protein of plasma membrane in various cells. A putative role of surface actin as the universal «non-hemostatic» center of plasminogen
activation is discussed. The exposition of cytoskeletal actin on the outer surface of cellular membrane is thought to
be a phenomenon, which is involved in both normal cell functioning and development of pathologies. In particular, the mechanism of plasminogen fragmentation on the surface of cancer cells mediated by actin, which results in generation of endogenous suppressors of tumor growth and metastazing (angiostatins), is described. It
has been acknowledged that the plasminogen/plasmin system in concert with surface actin regulates releasing
biologically active substances, e. g. catecholamines. The comprehensive assessment of plasminogen/plasmin
system and surface actin exposition is proposed to be a criterion of functional status of cells and can be used as a
diagnostic parameter at various pathologies.
Keywords: multifunctional proteins, plasminogen/plasmin system, actin. В огляді вперше проаналізовано та узагальнено літературні дані стосовно кооперації мультифункціональних білків: компонентів системи плазміноген/плазміну та актину. Розглянуто механізми, що лежать в основі міжмолекулярних взаємодій, та роль кринглових доменів плазміногену у міжбілковому
розпізнаванні. Особливу увагу приділено екстрацелюлярному актину, який виконує функції білка по верхні плазматичної мембрани різних клітин. Обговорюється можлива роль поверхневого актину як універсального «негемостатичного» центра активації плазміногену, а також функціональне значення експонування цитоскелетного білка різними клітинами за нормальних фізіологічних умов та при розвитку патологій. Зокрема, описано механізм фрагментації плазміногену на поверхні ракових клітин за участі актину з утворенням ендогенних супресорів пухлинного росту та метастазування – ангіостатинів і залучення системи плазміноген/плазмін та поверхневого актину до регуляції релізингу біологічно активних
речовин на прикладі катехоламінпродукуючих клітин. Комплексна оцінка стану плазміноген/плазмінової
системита актину пропонується як критерій функціонального статусу клітин, що може знай ти застосування у діагностиці різних патологій.
Ключові слова: мультифункціональні білки, система плазміноген/плазмін, актин. В обзоре впервые проанализированы и обобщены литературные
данные относительно кооперации мультифункциональных белков: компонентов плазминоген/плазминовой системы и актина.
Рассмотрены механизмы, лежащие в основе межмолекулярных
взаимодействий, и роль крингловых доменов плазминогена в межбелковом распознавании. Особое внимание уделено экстрацеллюлярному актину, выполняющему функции белка по верхности плазматической мембраны различных клеток. Обсуждается возможная роль поверхностного актина как униерсального «негемостатического» центра активации плазминогена, а так же функциональное значение экспонирования цитоскелетного белка разными
клетками при нормальных физиологических условиях и развитии
патологий. В частности, описан механизм фрагментации плазминогена на поверхности раковых клеток при участии актина с
образованием эндогенных супрессоров опухолевого роста и метастазирования – ангиостатинов и вовлечение системы плазминоген/плазмин и поверхностного актина в регуляцию релизинга биологически активных веществ на примере катехоламинпродуцирующих клеток. Комплексная оценка состояния плазминоген/плазминовой системы и актина предлагается в качестве критерия функционального состояния клеток и может найти применение в диагностике различных патоло гий.
Ключевые слова: мультифункциональные белки, система плазминоген/плазмин, актин.